The Impact of Gadget Use on Visual Abilities of School-Age Children: A Literature Review - Maulita, Firsilia Reza; Susanto, Tantut; Susumaningrum, Latifa Aini; Fauziah, Wahyuni (Al-Hijrah Indonesia, 2024)
Background: The use of gadgets for school-age children is useful for supporting the learning process, but excessive use is at risk of disrupting vision function if used for too long and can cause eye problems, including visual abilities. This can be caused by the level of use of gadgets in children. Purpose: The purpose of this study was to identify the impact of using gadgets on the visual ability of school-age children, especially those aged 6-12 years. Methods: The research design used in this literature study is a narrative review. The data collected in this study used secondary data from literature searches with online article search tools through databases, namely PubMed, SpringerLink, ScienceDirect, ProQuest, and Google Scholar. Article selection is carried out through 4 stages according to the PRISMA flowchart. Results: There are 10 articles analyzed in this study. The use of gadgets has an effect on decreasing the visual ability of school-age children due to frequent use for a long time. An overview of the impact of the use of gadgets on the visual ability of school-age children can be influenced by several factors, including the level of use which indicates the frequency and duration which indicates how often. Conclusions: The adverse effects of excessive use of gadgets on school-age children can be prevented by limiting the use of gadgets.